Educational Importance of Uzbek Folk Proverbs and English Folk Proverbs - Tulkinova Maftuna Hasan kizi; Ibragimova Hilola Bahodirjon qizi. (Zien Journals, 2023)
In this article, examining the educational significance of Uzbek and English folk proverbs and difference and similarities between them
Keywords: Uzbek language; English language; proverb; education